Identifying students' preference in delivering hands-on materials during Online Distance Learning (ODL) for multimedia course / Wan Anisha Wan Mohammad ... [et al.] - Wan Mohammad, Wan Anisha; Abdul Wahab, Naemah; Johan, Elly Johana; Mohd Mydin, Azlina Mohd Mydin (Unit Penerbitan JSKM, 2021)
Multimedia course is a course which does not only provide theoretical concepts to the students but at the same time hands-on materials on multimedia applications. This enable the students to enhance their knowledge on such applications and apply it in their studies. However, delivering hands-on materials especially on multimedia applications to students during online learning is very crucial to make sure that they can absorb the knowledge and understand all the features provided by the applications. A survey has been done in order to identify students ' preference in delivering hands-on materials during Online Distance Learning (ODL). Results show that most of the students prefer live hands-on class by the lecturer as they can see clearly all the features and functions shown by the lecturer during the live class.